CATEGORIZATION OF POVERTY IN THE REPUBLIC OF SERBIA IN THE PERIOD 2006-2010 - Grujić, Biljana; Roljević, Svetlana; Kljajić, Nataša (Economics of Agriculture, 2013)
The aim of this paper is overviewing a real picture of poverty in Serbia in the period 2006-2010, using the data of the Statistical Office of the Republic of Serbia (consumer price index - CPI) and the Social Inclusion and Poverty Reduction Unit (Cabinet of Deputy Prime Minister for European Integration of RS), as well as research results of relevant domestic and foreign literature. The percentage of the poor is categorized by: type of settlements, regional distribution, household type, age and participation of children and adults, level of education, and socio-economic status of the household. Survey results from 2010 pointed out that poverty is widespread among people living in rural area (13.6%), particularly among children under 13 years of age (13.7%), in Central Serbia (12.0%), in multi-member households (16.4%) and in households where the head has a lower educational level (14,2%) or is unemployed (17.9%). The fact that poor live in rural areas should not lead to deterioration of the principle of equality in the rights for all citizens of the Republic of Serbia.